Diagnosis of acute diverticulitis colon and its purulent – destructive complications - M. M. Mylytsia; O. B. Tymchuk; V. S. Kazakov (Сучасні медичні технології)
Aim. To determine the diagnostic effectiveness of clinical, laboratory and instrumental methods for detecting acute diverticulitis and its perforation complications.